Analysis Slope Stability Of River Embankment Stability And Proposed Remedial Work For Failure Slope At Muar River, Panchor, Johor - SAIDI, NUR HABIBAH; Alvin John Lim Meng Siang (Recent Trends in Civil Engineering and Built Environment, 2022)
This investigation aims to discover the reason of the collapse and to evaluate the slope stability so that remediation measures for stabilisation can be proposed at Muar River embankment, Panchor Town, Johor. A computer simulation of slope stability using Plaxis 2D to establish the overall displacement and safety factor is carried out for the purpose of easing investigations of failure cause. The river bank collapsed at 40m depth and the back analysis of the safety factor (FOS) is computed based on different height of the river embankment. The stimulation results showed that when the depth of the embankment is more than 30m, the slope failure has happened. In addition, the stimulation results in increased slope instability, since the moisture or pore-water pressure in the slope increases the soil’s shear strength or decreases it. FOS is determined is 1.069 when the slope 1 is stable. Therefore, there are three options of methods to be introduced to overcome the failure which are continuous sheet pile wall with tie back system, geogrid wall with pilling system and wellguard wall with pilling system.